Conservative treatment of the pulp in vital permanent teeth with incomplete rhizogenesis – a literature review (Research, Society and Development, 2023)
The aim of this study was to carry out a literature review about standard conservative treatments for cases of young permanent teeth, with incomplete rhizogenesis and pulp vitality, as well as the materials most used for this purpose. This is an integrative literature review. The studies were carefully evaluated and collected through searches on the research platforms of Pubmed, Scielo, BVS and Google Scholar, using the following terms: “Conservative Treatment”, “Pulp Capping” and “Endodontics”. After searching the electronic portals, 67 articles were found, in which the titles and abstracts were read, respecting the inclusion and exclusion criteria, thus electing 43 studies for detailed analysis. After evaluating the full text, 22 were excluded, leaving 21 articles based on this review. The techniques currently described in the literature for this purpose are: direct pulp capping, pulp curettage and pulpotomy, with calcium hydroxide and mineral trioxide aggregate (MTA) being the main materials used to carry out these procedures. The studies show that there is no significant difference between the two, regarding the pulp response and the continuity of the apical formation. It was concluded that direct pulp capping is currently the most performed and feasible procedure in cases of young permanent teeth with incomplete apex. Among the materials of choice, the most used for this procedure are calcium hydroxide and MTA, but MTA has shown more relevant biological properties.